SMART POWER METER BASED ON IOT - Saxena, Akash; Varshney, Upendra (International Journal of Psychosocial Rehabilitation, 2020)
IoT is a network used to interrelate multiple things including mechanical and computer machines. It passes data to a computer interface over the networks without the help of humans or computers. This enables control of various parameters, including electrical, physical and environmental parameters. The amount of electricity consumed is also a parameter to be measured. So to do this we need power meterwhich is much expensive. Thus, in this literature the proposed system adopts a basic portable low- cost power monitoring system with Wi-Fi capabilities. Different test results are provided to demonstrate the feasibility of our proposed IoT powered power monitoring system for calculating consumed electricity and secure data transmission via Wi-Fi module to the cloud server.